Changes in cellular processes occurring in mucopolysaccharidoses as underestimated pathomechanisms of these diseases. (10th January 2020) - Gaffke, Lidia; Pierzynowska, Karolina; Podlacha, Magdalena; Brokowska, Joanna; Węgrzyn, Grzegorz
Abstract: Mucopolysaccharidoses (MPS) are a group of genetic disorders belonging to lysosomal storage diseases. They are caused by genetic defects leading to a lack or severe deficiency of activity of one of lysosomal hydrolases involved in degradation of glycosaminoglycans (GAGs). Partially degraded GAGs accumulate in lysosomes, which results in dysfunctions of cells, tissues, and organs. Until recently, it was assumed that GAG accumulation in cells is the major, if not the only, mechanism of pathogenesis in MPS, as GAGs may be a physical ballast for lysosomes causing inefficiency of cells due to a large amount of a stored material. However, recent reports suggest that in MPS cells there are changes in many different processes, which might be even more important for pathogenesis than lysosomal accumulation of GAGs per se. Moreover, there are many recently published results indicating that lysosomes not only are responsible for degradation of various macromolecules, but also play crucial roles in the regulation of cellular metabolism. Therefore, it appears plausible that previous failures in treatment of MPS (i.e., possibility to correct only some symptoms and slowing down of the disease rather than fully effective management of MPS) might be caused by underestimation of changes in cellular processes and concentration solely on decreasing GAG levels in cells.